PENERAPAN SOFTWARE AKUNTANSI ACCURATE V.5 PADA PT. CIPTA KARYA LESTARI INDAH JAKARTA - Mujiaty, Yulia; Saridawati, Saridawati; Novayanti, Deasy; Wijayanti, Devi Ayu (EDUTECH CONSULTANT, 2019)
At this time the financial statements are the basic capital which is very important in measuring the performance of a company and making a calculated profit. A growing business utilizes the sophistication of computers using adequate applications, with calculations made that can be used as the company's foundation for making the right decisions for the company. PT. Cipta Karya Lestari Indah is a company engaged in the automotive sector, namely body repair services. One of the software that can help in the preparation of financial statements is the Accurate Accounting Accounting System Version 5 is easy to learn, understand, understand and easy to use in the field of business type, can be accessed the results of financial statements that are more accurate and in accordance with general financial accounting standards.